CAPACITY BUILDING POTENTIAL OF THE CALL CENTER SECTOR IN TURKEY - Ebru Seckin (European Regional Science Association (ERSA), 2010)
The firms prefer the lean production in the competitive environment, discard the stages and processes that do not create value by aiming at diversity in commodity and service provision. Accordingly, the relationships between the suppliers and customers become prominent and the firms that abandon the big firm emerge as new actors in the market. Information and communication technology brings about flexibility and creates new opportunities in location choice. Thus, the enterprises have become complicated, distant from the center and network based. As the central tasks within a firm stay in the developed regions, the peripheral tasks are moved to underdeveloped regions. As a result of the core-periphery distinction in service sector, call center sector has become prominent. When the issue is considered in terms of regional development, the call centers, which are now out of the firm, are located in the underdeveloped regions. While the literature about call center sector discussion considers call centers as an opportunity for the economic development of the underdeveloped regions, making use of the labor force of the periphery at the call centers seems to be the greatest constrains. The aim of this study is to evaluate whether the call centers are long term investments for underdeveloped regions, in terms of its contribution to the development of the local labor force capacity. The goal is to compare the opinions of the labor force about the jobs at the call center related to the characteristics of the labor force. In this respect, the methodology consists of a survey study with the employees of two call center firms. The employees answered 20 questions about their willingness to continue their job at the call center and capacity development by utilizing 5 Likert scale. The results will be obtained by means of ANOVA test that is conducted in order to determine whether there is a difference in the answers provided according to the level of education, type of the firm, term of employment and gender.
Keywords: 330